Implementasi Program Dinamik dalam Optimisasi Biaya Persediaan Perusahaan : Implementasi Program Dinamik dalam Optimisasi Biaya Persediaan Perusahaan - Bella Syahrani Nasution; Fibri Rakhmawati; Nenna Irsa Syahputri (FMIPA Universitas Papua, 2023)
This research is to reduce the total cost of the company’s inventory and minimize losses. Dynamic programming method is one of the methods used to manage inventory. Calculations using the dynamic programming method can be carried out by multiplying the product price per unit by the amount of production that has been forecast and converted to the inventory method and by multiplying the holding cost per unit of product by the amount of inventory at a certain time and then the two multiplications are added up. The advanced dynamic program is calculated from the first month to the last month. The dynamic program backwards is carried out from the end of the month to the beginning of the month. The research objective is to reduce the company’s total inventory costs of the dynamic program in the amount of Rp.n88,765,982,655 from January 2022 – August 2022.